Biocatalytic Nanomaterials: A New Pathway for Bacterial Disinfection. Issue 33 (3rd July 2021) - Fan, Xin; Yang, Fan; Nie, Chuanxiong; Ma, Lang; Cheng, Chong; Haag, Rainer
Abstract: Clinical treatment of pathogenic infection has emerged as a growing challenge in global public health. Such treatment is currently limited to antibiotics, but abuse of antibiotics have induced multidrug resistance and high fatality rates in anti‐infection therapies. Thus, it is vital to develop alternative bactericidal agents to open novel disinfection pathways. Drawing inspiration from elements of the human immune system that show great potential for controlling pathogens or regulating cell apoptosis, the design of biocatalytic nanomaterials (BCNs) have provided unrivaled opportunities for future antibacterial therapies. More significantly, BCNs exhibit various superior properties to immune cells and natural enzymes, such as higher biocatalytic performance, extraordinary stability against harsh conditions, and scalable production. In this review, the most recent efforts toward developing BCN‐based biomedical applications in combating bacterial infections are focused upon. BCNs' antibacterial mechanisms, the classification of BCNs, antibacterial activities that can be triggered or augmented by energy conversion, and the eradication of biofilms with BCNs are systematically introduced and discussed. The current challenges and prospects of BCNs for biocatalytic disinfection are also summarized. It is anticipated this review will provide new therapeutic insights into combating bacteria and biofilms and offer significant new inspiration for designing future biocatalytic nanomaterials. Abstract : Recent advancements toward developing biocatalytic nanomaterials (BCNs) as a new pathway for bacterial disinfection are systematically reviewed. The antibacterial mechanism, classification of BCNs, energy‐conversion‐triggered or augmented biocatalytic activities, and biofilms' eradication are thoroughly discussed. Besides, the challenges and prospects for biocatalytic disinfection are summarized. This review may offer abundant inspirations for designing new BCNs for combating bacteria/biofilms.